Analisis Penggunaan Media Komunikasi Online terhadap Partisipasi Kerja Kelompok Mahasiswa Universitas Brawijaya Secara Daring - Alifdaffa Nurfahmi Dekatama; Diah Priharsari; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
During the Covid-19 pandemic, all universities conducted online teaching and learning activities using online communication media. The purpose of this study is to explore in depth what are the uses of online communication media in Brawijaya University students and the influence of using online communication media on group work participation by Brawijaya University students. In this study, researchers used qualitative methods with semi-structured interview data collection techniques and analyzed using thematic analysis methods. In the thematic analysis method, there are six stages, namely (1) Understanding the data, (2) Creating codes, (3) Searching for themes, (4) Reviewing themes, (5) Defining and naming themes, and (6) Making analysis results. . After the researchers got the findings from the results of the analysis that had been done, the researchers conducted a research quality test to determine the quality of the results of the research made. In the research quality test, this study met two parameters, namely the depandability test and the confimability test. Based on interviews conducted by researchers, they found that the use of online communication media by Brawijaya University students was mainly for group work activities as Discussion and Tasks. As for the participation itself, online communication media have an impact on the participation, activeness, and motivation of students in conducting online group work activities.